A viscosity measurement during the high pressure phase transition in triolein - Siegoczyński, R M; Rostocki, A J; Kielczyński, P; Szalewski, M (Journal of physics. Conference series, 2008)
The high-pressure properties of triolein, a subject of extensive research at the Faculty of Physics of Warsaw University of Technology (WUT) have been enhanced by the results of viscosity measurement within the pressure range up to 0.8 GPa. For the measurement the authors have adopted a new ultrasonic method based on Bleustein-Gulyaev waves, successfully developed earlier for the low pressures in the Section of Acoustoelectronics of the Institute of Fundamental Technological Research. The measurements have shown: 1. Exponential rise of viscosity with pressure up to 0.5 GPa. 2. Extraordinary increment of viscosity at constant pressure during phase transition. 3. Further exponential rise of viscosity with pressure of the high-pressure phase of triolein. 4. The pressure exponents of the viscosity of both phases were different (the high-pressure phase had much smaller exponent). 5. The decomposition of the high pressure phase due to the slow decompression have shown very large hysteresis of viscosity on pressure dependence.